2021
DOI: 10.3390/pharmaceutics13060837
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D—Managing the Delicate Balance

Abstract: Lysosomal proteases play a crucial role in maintaining cell homeostasis. Human cathepsin D manages protein turnover degrading misfolded and aggregated proteins and favors apoptosis in the case of proteostasis disruption. However, when cathepsin D regulation is affected, it can contribute to numerous disorders. The down-regulation of human cathepsin D is associated with neurodegenerative disorders, such as neuronal ceroid lipofuscinosis. On the other hand, its excessive levels outside lysosomes and the cell mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 147 publications
2
29
0
Order By: Relevance
“…Tamoxifen. It increases the production of cathepsin D, which helps to prevent this disease from occurring since it has been shown that many neurodegenerative diseases arise when there are low levels of cathepsin D or it is inactive, causing failures in one of the genes that produces this disease [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tamoxifen. It increases the production of cathepsin D, which helps to prevent this disease from occurring since it has been shown that many neurodegenerative diseases arise when there are low levels of cathepsin D or it is inactive, causing failures in one of the genes that produces this disease [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peptide mediated inhibition of BACE-2 and CTSD could also be a beneficial therapy since BACE-2 plays a significant role in enhanced neurodegeneration in Alzheimer's disease, tumor progression such as in glioma, melanoma etc. (Farris et al 2021) and CTSD is also involved in various neurodegenerative disorders and cancers such as melanoma, breast cancer, prostate cancer etc (Mijanovic et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Through its endopeptidase activity, CatD modulates the activity of diverse polypeptides, growth factors, and enzymes and the degradation of misfolded, long‐lived, and denatured proteins. Accordingly, CatD is considered an essential regulator of cell signaling and cellular homeostasis [ 31 ]. Dysregulated CatD activity plays an important role in diseases such as acute kidney injury, coronary events, neurodegenerative diseases, and cancer (reviewed in [ 31 , 32 , 33 , 34 ]).…”
Section: Lysosomal Peptidasesmentioning
confidence: 99%
“…Accordingly, CatD is considered an essential regulator of cell signaling and cellular homeostasis [ 31 ]. Dysregulated CatD activity plays an important role in diseases such as acute kidney injury, coronary events, neurodegenerative diseases, and cancer (reviewed in [ 31 , 32 , 33 , 34 ]).…”
Section: Lysosomal Peptidasesmentioning
confidence: 99%